Review on special emphasis of bortezomib on relapsed/refractory myeloma - Talaviya, Praful A.; Vyas, Bhavesh M.; Indoria, Shashi P.; Modh, Vipul B. (International Journal of Research in Medical Sciences, 2017)
Refractory or relapsed Multiple Myeloma (MM) is a plasma cell neoplasia characterized by paraproteins in the urine or serum and a bone marrow plasmacytosis of over 10%. Multiple/refractory myeloma is a neoplasm of plasma cells and exact cause of multiple myeloma is remain unidentified, it is characterized by accumulation of malignant plasma cells in the bone marrow, leading to bone marrow failure, anemia, skeletal destruction, renal failure, increased susceptibility to infection and hypercalcemia. The survival time for the patients with refractory or multiple myeloma can be prolonged with treatment of newer and more target specific approach. The proteasome inhibitors are an important class of anti-myeloma drugs that have efficacy to disrupt the proteolytic structure of tumor cells and enhancing their susceptibility to apoptosis. Bortezomib has a significant clinical efficacy against refractory multiple myeloma. Bortezomib is the most commonly used and clinically tested proteasome inhibitor and which is effective in prolonging the overall survival in several trials. Bortezomib combinations with other drugs such as dexamethasone and cyclophosphamide are the choice of treatment for standard risk patients following the mSMART guidelines. The success with lower dosage of bortezomib in elderly patient’s proven efficacious subcutaneous usage and its useful proteasome inhibitor to enhance patient’s compliance and reduces toxicity and costs of therapy. This review discusses on special emphasis of bortezomib on relapsed/refractory multiple myeloma as front-line treatment.